Hubungan Kebiasaan Merokok dengan Kejadian Hipertensi - Aufa Fitri Rahmatika (Jurnal Medika Hutama, 2021)
Blood pressure is the force exerted by blood on the walls of the blood vessels and is generated by the force of blood against the artery walls when the blood is pumped from the heart to the tissues. The amount of pressure varies depending on the state of the blood vessels and heart rate. Hypertension is an increase in systolic pressure greater than or equal to 160 mmHg and or diastolic pressure equal to or greater than 95 mmHg, JNC VII argues hypertension is an increase in blood pressure above 140/90 mmHg. Hypertension is the silent disease because people do not know they have hypertension before having their blood pressure checked. One of the factors that can increase the potential for hypertension is smoking. The nicotine in cigarettes can affect a person's blood pressure, either through the formation of atherosclerotic plaques, the direct effect of nicotine on the release of the hormones epinephrine and norepinephrine, or through the effect of CO in increasing red blood cells. In smokers, there is an increase in the amount of c-reactive protein and natural inflammatory agents which can cause endothelial dysfunction, damage to blood vessels and stiffness of artery walls which leads to an increase in blood pressure.